Kehadiran Ibadah Online dalam Masa Covid-19 bagi Umat: dalam Filsafat Dekontrutif - Maria Puspitasari (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2020)
Abstract This research is a study of the practice transition of the on-site services previously conducted on churches to online services from the parish’s respective residences. This condition occurs due to the Covid-19 pandemic. In Indonesia, the abolition of all kinds of communal meeting has been legally regulated and issued by both the central and regional governments. This is one of the Government’s ways to terminate the spread of Covid-19. On the other hand, the service experiences significant semantic change and it makes the parish acquire a new understanding of the term. In analyzing this reconstructed meaning, qualitative literary research is employed along with biblical perspective in interpreting the service and Derrida's deconstructive philosophy studies. Hence, this research has its own practical significance so that the parish members are able to find out the meaning of this online service appropriately. The conclusions of this research state that the church service must be well understood as a form of lifetime offering and an everlasting dedication to God. The genuine meaning of the service itself cannot be vexed merely by its trivial setting of place or method. Service is all about how a person consecrates one’s life to God. Abstrak Penelitian ini adalah sebuah kajian tentang peralihan praktik ibadah gereja-gereja yang sebelumnya dilakukan secara tatap muka di tempat ibadah dan kini beralih menjadi secara online dari rumah masing-masing. Hal ini disebabkan adanya pandemi Covid-19. Di Indonesia, baik Pemerintah pusat dan daerah mengeluarkan peraturan untuk meniadakan segala macam pertemuan yang mendatangkan banyak orang. Hal ini merupakan salah satu cara Pemerintah untuk memutus penyebaran Covid-19. Di sisi lain, peribadahan mengalami pergeseran makna dan menyebabkan umat membangun pemahaman baru mengenai ibadah. Dalam menganalisis hal pemaknaan kembali dari ibadah gereja, peneliti menggunakan metode penelitian kualitatif literatur melalui interpretasi ibadah dalam perspektif Alkitab dan kajian filsafat dekonstruktif Derrida. Penelitian ini penting agar umat mampu memaknai ibadah online secara tepat. Kesimpulan penelitian ini adalah bahwa ibadah harus dipahami sebagai persembahan seluruh kehidupan dan sebagai pengabdian kepada Tuhan. Peribadahan tidak bisa direduksi oleh tempat atau cara melakukannya. Peribadahan adalah bagaimana seorang mempersembahkan hidupnya kepada Tuhan.